2020
DOI: 10.46332/aemj.792717
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Features of the Patients With Covid-19: Typical and Atypical Findings

Abstract: Bu çalışmada COVID-19 tanısı alan hastaların toraks bilgisayarlı tomografi (BT) sonuçlarını inceleyip, tipik ve atipik bulguları literatür eşliğinde sunmayı amaçladık.Araçlar ve Yöntem: Hastanemize mart ve nisan aylarında başvuran ve reverse transkriptaz-polimeraz zincir reaksiyonu (RT-PZR) ile COVID-19 tanısı alan hastaların toraks BT'leri retrospektif olarak değerlendirildi. Akciğer parankim bulgularından buzlu cam sahaları, konsolidasyon, vasküler genişleme, fibrozis, nodül, septal kalınlaşma (crazy paving)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…When seen with diffuse ground-glass and consolidation, it indicates disease progression or peak period. [10,14,15] Ground-glass opacity was found in 88% of patients in a meta-analysis by Salehi et al, and was reported as the most common imaging finding [16] : Similarly, the most common imaging finding in our study was ground-glass opacity.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…When seen with diffuse ground-glass and consolidation, it indicates disease progression or peak period. [10,14,15] Ground-glass opacity was found in 88% of patients in a meta-analysis by Salehi et al, and was reported as the most common imaging finding [16] : Similarly, the most common imaging finding in our study was ground-glass opacity.…”
Section: Discussionsupporting
confidence: 75%
“…Bilateral, peripheral, and multifocal (patchy) foci in the middle and lower zones, ground-glass areas, consolidation, a combination of both findings, and vascular enlargement are the most common. [ 10 , 13 ] Most of the patients’ CT reports in our study were reported as typical findings.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations